Delayed Endothelial Progenitor Cell Therapy Promotes Bone Defect Repair in a Clinically Relevant Rat Model. (30th March 2017) - Bates, Brent D.; Godbout, Charles; Ramnaraign, David J.; Schemitsch, Emil H.; Nauth, Aaron
Abstract : The repair of segmental bone defects remains a significant challenge for orthopaedic surgeons. Endothelial progenitor cells (EPCs) have successfully promoted the repair of acute defects in animal models; however, the ability of EPCs to induce the repair of chronic nonhealing defects, such as those often encountered clinically, has not been investigated. Therefore, the purpose of this study was to investigate the ability of EPCs delivered in delayed fashion to induce the repair of nonhealing defects in a clinically relevant model. In order to simulate delayed treatment, 5 mm segmental defects in Fischer 344 rat femora were treated with bone marrow-derived EPCs on a Gelfoam scaffold at 3 weeks post creation of the defect. At ten weeks posttreatment, 100% of EPC-treated defects achieved union, whereas complete union was only achieved in 37.5% of defects treated with Gelfoam alone. Furthermore, significant increases in ultimate torque (p = 0.022 ) and torsional stiffness (p = 0.003 ) were found in EPC-treated defects compared to controls. Critically, no differences in outcomes were observed between acute and delayed EPC treatments. These results suggest that EPCs can enhance bone healing when applied in an acute or delayed fashion and that their use may represent a clinically translatable therapy for bone healing in humans.